TOWARDS APPLYING A MANAGEMENT SOFTWARE SOLUTION ON MULTI-LEVEL CLASSES: A CASE STUDY OF TWO ORAL ACTIVITY LESSONS IN FRENCH SUBJECT - Drissi El Bouzaidi, Rachid; Chaiba, Abdellah; Rahal, Mahmoud (International Online Journal of Education and Teaching, 2020)
This work was motivated by the idea of ​​approaching teaching practice in multilevel classes based on a problem, namely the need to improve the management of time in these types of classes. The time management strategy, developed in this work, consists of applying two modes of alternating teaching, the classical mode "work and make work" and the "actual - virtual" presence of the teacher mode using the software Netsupport School. The aim of this paper is to study the impact of the application of this software solution in two heterogeneous lessons of the French language, specifically of oral activity, for a subgroup of a double-level class (2nd Primary Year + 3rd Primary Year). The obtained results are conclusive since this approach has made it possible to reduce dead time and the teacher’s great effort and to involve strongly the learners in the construction of the concepts.